Perceptions of service quality and behaviour intentions of campus fitness center users in Malaysia and Thailand - Yusof, Aminuddin; Popa, Arporn; Soh, Kim Geok (Human Resource Management Academic Research Society, 2018)
The study was designed to determine the perceptions of service quality and future intention to use campus fitness centers in Universiti Putra Malaysia (UPM) and Mahasarakham University, Thailand. Data were collected using questionnaires distributed to 450 campus fitness center users comprising of faculty and staff from Mahasarakham university (n=250) and one university in UPM (n=200) were selected to participate as subjects in the study. The questionnaire consisted of items based on the Likert-scale Service Quality Assessment Scale (SQAS) developed by Lam, Zhang and Jensen (2005). Behavioral intention is based on three questions modified from Cunningham and Kwon (2003) and Zeithaml et al. (1996). Results showed significant differences (p<.05) in perceptions of overall fitness facility service quality and overall program service quality between users in UPM and Mahasarakham universities. The results showed a statistically significant difference (p<.05) in terms of behavior intentions of users in UPM and Mahasarakham University with those in UPM reporting higher intentions to renew their membership and recommend the recreation center to other people. Based on the results, it was concluded that good quality service would influence fitness center users at both universities to recommend the fitness center to other people and influence them to renew their membership.